Youth development and spatial configurations: socio-spatial inequalities in Palestinian refugee camps in Lebanon - El-Zakka, Yara; Diab, Jasmin Lilian (Frontiers in Sociology, 2023)
This article explores the intersectional fields of displacement and architecture by examining the interrelationship between youth development and spatial configurations in Palestinian refugee camps in Lebanon, more specifically in Ein El Hilweh Camp, South of the country. It aims at understanding how spatial configurations can alter human behavior, and the ways in which societal reform can take place in an urban context. Through taking Ein El Hilweh Camp as a case study and field interviews with experts working and residing in the Ein El-Hilweh Camp, this article asserts that youth development in Palestinian Camps in Lebanon is hindered by the dire conditions of spatial configurations in the camps and their geopolitics. It also asserts that in the presence of fostered youth protection and capacity and skills building, youth engagement and participation in the modification of their spaces act as essential drivers of change which contribute to the reduction of urban poverty and to the development of urban strategies that can sustain their development and provide an incubating environment for them to grow during the stages of their youth and beyond. Moreover, this article suggests that the primary factor contributing to the hindered situation of Palestinian refugees in Lebanon is the condition of permanent temporariness imposed by the state. The reduction of socio-spatial inequalities is temporary unless the integration of Palestinian refugees is fostered and their accessibility to social, economic, and civil rights, as well as the right to the city is granted.